Hawkins e o mundo invertido: análise dos mundos possíveis de stranger things - Figueiredo, Jéssica Maria Brasileiro de (2018)
This dissertation aims to analyze the two textual worlds presented in the series Stranger Things. To that end, literature reviews were carried out on the notions of possible worlds covered in philosophy and literary studies, from the textual actual world concepts supported by the author Marie-Laure Ryan (1991), as well as a descriptive analysis of the narrative and visual articulations, which point to the presence of these two worlds. We start with the assumption that the Upside Down is a second world in history, existing in parallel with the city where the series happens, Hawkins, where the characters live. The discovery of this second world is guided by the investigations that the own personages develops, when trying to discover the whereabouts of the boy Will Byers, disappeared at the beginning of the series. Thus, each new discovery made about the disappearance of the boy reveals aspects of the existence of a parallel world, which is later called Upside Down. To analyze this process, we anchor ourselves in the studies of Aristotle (1959) on recognition in a fable of fiction. From this articulation, it was possible to observe how the characters pass from the unknown to the known, and identify the aspects of the Upside Down that are presented throughout the series. The corpus of this work was composed by the eight episodes that compose the first season of the series (Netflix, 2016). The analysis was carried out around two processes: a) description of the narrative articulations of the series, considering the development of acts and arcs, which provides a detailed verification of the serial structure of this production; b) description of sequences of scenes, illustrated by frames, to evidence the moments when the characters discover aspects about the Upside Down. This last analysis is carried out with contributions in the studies of Jeremy Butler (2009) on television style. The results obtained evidenced the presence of these two worlds in Stranger Things, which are called in this work two textual actual worlds, and indicate a change in the perception of the characters about their own familiar world, from the complete understanding that there is an Upside Down world in the universe of this fiction.